2022
DOI: 10.32598/cmja.12.2.18.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Self-care Training Program Based on Temperament Modification on the Quality of Life of Patients with Type 2 Diabetes

Abstract: Objective: Considering the high prevalence of diabetes mellitus and its effect on the quality of life (QoL) of patients which can lead to low self-care and increased risk of disease complications, this study aims to assess the effect of a self-care training program based on temperament modification on the QoL of patients with type 2 diabetes (T2D). Methods: In this quasi-experimental study, 110 patients with T2D were selected by a convenience sampling method and were randomly divided into two groups of interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…In order to determine the QOL in people, the results of the present study are somewhat consistent with the results of some studies in Korea (18) and in Iran (5).In the study in China, the total QOL was reported lower than the current study. This difference may be due to cultural differences of the research communities and inclusion criteria.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to determine the QOL in people, the results of the present study are somewhat consistent with the results of some studies in Korea (18) and in Iran (5).In the study in China, the total QOL was reported lower than the current study. This difference may be due to cultural differences of the research communities and inclusion criteria.…”
Section: Discussionsupporting
confidence: 90%
“…(4). These complications also have adverse effects on various aspects of patients' lives, including their mental, physical, social, economic, family life, and sexual function (5). Due to the shame caused by the stigma of the disease, these individuals are less likely to discuss problems they may have in managing their disease (6).…”
Section: Introductionmentioning
confidence: 99%